The fascination of the West and the ambivalence of the Byzantines towards it through the case of Demetrios Kydones - Tripoula, Ioanna (Dia-noesis: A Journal of Philosophy, 2024)
This paper focuses on the case of the politician and scholar Demetrios Kydones as typical of the fascination that the West exerted on the Byzantines, but also of the ambivalence towards it. First, there is a brief overview of the events of his life, which encouraged his contact with the Latins. A more detailed reference was made to his translation, writing, and teaching. In our view, his provocative positions were the reason he had not received the recognition he deserved to this day. His most important value lies in the fact that, in an age of hostility, he sought to bring Byzantium closer to the West by presenting logical and valid arguments beyond petty political pursuits and prejudices.